The relationship between trait awe and teachers’ well-being for primary and secondary school teachers: the roles of professional identity and work engagement - Rong-Mao Lin; Wan-Qing Zheng; Yan-Ping Chen; Yu-Shan Ye; Tian-Xiang Hu; Shan-Shan Xie (BMC Psychology)
Abstract Promoting teachers’ deep, sustainable well-being is vital for educational development, but the key emotional resources involved are still not well understood. Drawing on the broaden-and-build theory of positive emotions, this study is the first to model how trait awe influences occupational well-being among primary and secondary school teachers. We conducted a cross-sectional survey with 1,037 teachers in China and used structural equation modeling for data analysis. Results showed that trait awe enhanced teachers’ well-being both directly and indirectly. The indirect effect was mediated by professional identity and work engagement, both independently and sequentially. These findings provide the first empirical evidence that cultivating trait awe can be a powerful lever for supporting teachers’ well-being and driving educational progress.